High risk HPV types 18 and 16 are potent modulators of oral squamous cell carcinoma phenotypes in vitro - Johnson Devin (Infectious Agents and Cancer, 2007)
Abstract Background Human papillomavirus (HPV) has been confirmed as the primary etiological factor that transforms cervical epithelia into cancer. The presence of HPV in oral cancers suggests that HPV may play a similar role in transforming the oral epithelia. A high degree of variability in the prevalence of HPV in oral cancers has been found, however, raising questions regarding its role in the transformation and development of oral cancers. The goal of this study was to test our hypothesis that high-risk HPV strains HPV16 and HPV18 will alter the phenotype of transformed oral squamous cell carcinoma cell lines, CAL27, SCC-15 and SCC-25 in vitro. Results CAL27 cells transfected with HPV18, HPV16, as well as HPV16/18 co-transfectants, demonstrated significant increases in proliferation, adhesion and cell spreading compared with non-transfected controls. These observed differences were correlated with a small level of increased cell survival. SCC-15 cells, however, displayed a differential response to HPV transfection, with only HPV18-transfectants demonstrated changes to proliferation. Interestingly, SCC-25 cells displayed a more complex response, with HPV16-induced increases in cell proliferation, viability and cell spreading, while HPV18- and 16/18-transfectants exhibited reduced adhesion and proliferation. Conclusion Determining the potential of specific high-risk HPV strains to alter phenotypic behaviors of already transformed oral carcinomas is a critical step in providing more accurate prognosis and treatment options for oral cancer patients. The identification of differential responses to specific HPV strains among oral cancers suggests a more significant, complex and multifactorial role of HPV, not only in transforming, but also in modulating, the phenotype and treatment responsiveness of precancerous and cancerous oral lesions. This study provides some of the first evidence to help identify the important molecular markers for pathways that could be used to determine the most effective and appropriate treatment plans for oral cancer patients with concomitant oral HPV infections.